Eco-Friendly Pretreatment and Dyeing of Cotton with Vat Yellow 46. Issue 14 (28th October 2022) - Kamran, Muhammad; Adeel, Shahid; Rehman, Fazal-ur-
ABSTRACT: Sustainable energy tools are nowadays giving popularity in all the fields particularly in textiles due to their effective mode of action. The current study has been aimed to apply these tools (ultrasonic and microwave) for fabric treatment followed by vat dyeing using vat yellow 46 dye. Ultrasonic heating up to 60 and microwave up to 6 min were employed before and after the fabric treatment process. Various dyeing parameters were optimized as per ISO standards. Color characteristics of dyed fabric were assessed. It is found that microwave treatment of 4 min should be given to bleached fabric for vat dyeing with non-radiated dye solution (NRS), whereas ultrasonic treatment of 40 min should be given to bleached fabric for vat dyeing with non-radiated dye solution (NRS) and irradiated cotton (RC) fabrics. FTIR analysis reveals that there is no chemical change in the functional peak of cellulosic before and after ultrasonic and microwave treatment was found. It is concluded that these sustainable tools have not only reduced time cost and labor but also improve the vat dyeing process.